Kajian Aplikasi Pupuk Organik Pada Tumpang Sari Tanaman Kelor-Selada Di Lahan Kering - I Gusti Made Arya Parwata; I Komang Damar Jaya; Bambang Budi Santoso; Jayaputra Jayaputra (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
Lettuce and Moringa are recently popular vegetable crops because their demand improves significantly, and their development lead to dry land because its potencial in Indonesia is still high.  The use of dry land should be followed by applying inter cropping technique in order to make plant micro climate becomes more favourable. In addition, low soil fertility and intensive ussage of inorganic fertilizers makes the application of organic fertilizers imperative. The objective of the research is to investigate the type of organic fertilizer giving high yield of lettuce and moringa cultivated using inter cropping technique in dry land. The results showed that the organic fertilizers applied improved the plant growth and yield, and also improved the land equivalent ratio (LER).  The highest LER was showed by apllication of Organox, followed by  Bio Extrim and Biota Plus, and the lowest one showed by without organic fertilizer application.